(untitled) (NAU Journal of Library and Information Science, 2023)
This paper examined knowledge-sharing and innovation capabilities of academic library professionals of Babcock University in Ogun State. A survey research design was adopted for the study. The population of the study comprised forty-nine library staff at Babcock University. A self-structured questionnaire was used, and the total enumeration method was also used for sampling while collected data were analyzed with descriptive statistics. The findings of the study showed that academic library professionals at Babcock University utilize marketing, technological/service, and organizational innovations to discharge their duties. The study found that 91.8% of the respondents strongly agreed that new services are provided through mobile applications and user-friendly interface to meet user needs. Similarly, 85.7% of the respondents strongly agreed that they share knowledge with colleagues through notice boards, WhatsApp, bulletin, symposia, lectures, conferences, training, and mentoring. It was concluded that academic library professionals should inculcate knowledge sharing through innovation capabilities for user satisfaction.